(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
In the article, the methodological system for improving the professional culture of students of higher educational institutions based on economics is a model for improving the professional culture of students based on economics,active participation in socio-economic, cultural, educational, and spiritual spheres, emphasizing the importance of developing the professional culture of a responsible, enthusiastic person who has achieved the position of a citizen.